Intermediate-Term Hip Survivorship and Patient-Reported Outcomes of Periacetabular Osteotomy: The Washington University Experience. (7th February 2018) - Wells, Joel; Schoenecker, Perry; Duncan, Stephen; Goss, Charles W.; Thomason, Kayla; Clohisy, John C.
Update: This article was updated on February 7, 2018, because of a previous error. On page 219, in Figure 1, the text that had read "122 Preserved Hips (WOMAC Pain Score <10, mHHS >70 and THA)" now reads "122 Preserved Hips (WOMAC Pain Score <10, mHHS >70 and No THA)". Background: The Bernese periacetabular osteotomy (PAO) is an alternative to arthroplasty for treating symptomatic acetabular dysplasia, but there have been few studies on the intermediate-term outcomes of this procedure. In the present study, we assessed intermediate-term hip survival and patient-reported outcomes of PAO used to treat symptomatic acetabular dysplasia. Methods: From July 1994 to August 2008, 238 hips (206 patients) were treated with PAO. Sixty-two had a diagnosis other than classic acetabular dysplasia, and 22 were lost to follow-up. The remaining 154 hips (129 patients) were evaluated at an average of 10.3 years postoperatively. Kaplan-Meier analysis was used to assess survivorship with an end point of total hip arthroplasty (THA). Hips were evaluated using the University of California at Los Angeles (UCLA) Activity Score, modified Harris hip score (mHHS), and Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) pain subscale score. A WOMAC pain subscale score of ≥10 and/or an mHHS of ⩽70 were considered to indicate a clinically symptomatic hip. Results: Kaplan-Meier analysis revealed a hip survival rate of 92% (95% confidence interval [CI]: 82% to 97%) at 15 years postoperatively. Eight hips (5%) underwent THA at a mean (and standard deviation) of 6.8 ± 5.2 years. Twenty-four additional hips (16%) were considered symptomatic based on a WOMAC pain score of ≥10 and/or an mHHS of ⩽70. One hundred and twenty-two hips (79%) did not undergo THA and did not meet the criteria for symptoms, and these hips had a mean mHHS of 92.4 ± 8.4, WOMAC pain subscale score of 1.2 ± 1.9, and UCLA Activity Score of 7.7 ± 2.0 at a mean of 10.1 years. A higher risk of failure was associated with fair or poor preoperative joint congruency (odds ratio [OR]: 8.65; 95% CI: 1.18 to 63.55; p = 0.034) and with a postoperative lateral center-edge angle of >38° (OR: 8.04; 95% CI: 2.01 to 32.22). A concurrent head-neck osteochondroplasty was associated with a decreased risk of failure (OR: 0.27; 95% CI: 0.09 to 0.78; p = 0.016). Conclusions: This study demonstrates the durability of the Bernese PAO. Fair or poor preoperative joint congruency and excessive postoperative femoral head coverage were found to be predictors of failure, while concurrent head-neck osteochondroplasty in patients with an inadequate range of motion after PAO was associated with a decreased risk of failure. Level of Evidence: TherapeuticLevel IV . See Instructions for Authors for a complete description of levels of evidence.